2017
DOI: 10.1016/j.psychres.2016.12.011
|View full text |Cite
|
Sign up to set email alerts
|

A quick behavioral dichotic word test is prognostic for clinical response to cognitive therapy for depression: A replication study

Abstract: There are no commonly used clinical indicators of whether an individual will benefit from cognitive therapy (CT) for depression. A prior study found right ear (left hemisphere) advantage for perceiving dichotic words predicted CT response. This study replicates this finding at a different research center in clinical trials that included clinically representative samples and community therapists. Right-handed individuals with unipolar major depressive disorder who subsequently received 12–14 weeks of CT at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…In another study, responders to CT showed twice the mean right ear advantage in dichotic fused words performance than non-responders. Patients with a right ear advantage greater than healthy controls had an 81% response rate to CT, whereas those with performance lower than controls had a 46% response rate ( Bruder et al., 2017a , b ). Individuals with a right ear advantage, indicative of strong left hemisphere language dominance, may be better at utilizing cognitive processes and left frontotemporal cortical regions critical for success of CT for depression.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…In another study, responders to CT showed twice the mean right ear advantage in dichotic fused words performance than non-responders. Patients with a right ear advantage greater than healthy controls had an 81% response rate to CT, whereas those with performance lower than controls had a 46% response rate ( Bruder et al., 2017a , b ). Individuals with a right ear advantage, indicative of strong left hemisphere language dominance, may be better at utilizing cognitive processes and left frontotemporal cortical regions critical for success of CT for depression.…”
Section: Introductionmentioning
confidence: 88%
“…EEG alpha asymmetry at rest and during cognitive or emotional tasks are consistent with reduced left prefrontal activity, which may impair downregulation of amygdala response to negative emotional information. Dichotic listening and visual hemifield findings for non-verbal or emotional processing have revealed reduced right-lateralized responsivity in depressed patients to emotional stimuli in occipitotemporal or parietotemporal cortex ( Bruder et al., 2017a , b ). Individual differences of right-left brain function are related to diagnostic subtype of depression, comorbidity with anxiety disorders, and clinical response to antidepressants or cognitive behavioral therapy.…”
Section: Introductionmentioning
confidence: 99%